Overview of the subgenus Ventocoris s. str. (Hemiptera: Heteroptera: Pentatomidae) with new records and a revised key to the Ventocoris species of Turkey - Dursun, Ahmet; Fent, Meral (Zootaxa, 2013)
This paper presents an overview of the nominotypical subgenus of the genus Ventocoris Hahn, 1834 (Hemiptera: Het-eroptera: Pentatomidae: Podopinae); the two species are identified, redescribed, illustrated, and keyed. Species of the sub-genus Astirocoris Jakovlev, 1894 known in Turkey are redescribed, a key is provided for the Turkish species of Ventocoris. Ventocoris trigonus (Krynicki, 1871), Ventocoris nigellae (Fabricius, 1787) and V. advena (Horváth, 1896), syn. nov., are synonymized with V. rusticus (Fabricius, 1781). The first records of V. falcatus (Cyrillus, 1791) from Malta and V. oblongus (Horváth, 1889) from Turkey are given.